Nano-Metal Hydrogen Therapy Targeting Immune Cells Drives Synergistic Anti-Tumor Effects - Yuxuan Ding; Min Ma; Jianing Wang; Zixin Zhang; Jingyu Wu; Linxiang Zhou; Xiaoyan Cao; Libing Liu (Molecules, 2026)
Hydrogen is employed as a therapeutic gas in the treatment of stroke, tissue repair, and cancer, owing to its excellent biocompatibility, antioxidant properties, anti-inflammatory effects, and regulation of cellular metabolism. Moreover, nanometallic materials generate hydrogen through pH-responsive, light-responsive, ultrasound-responsive, and electrical stimulation and play a pivotal role in cancer therapy by activating anti-tumor immune responses, reversing immunosuppressive microenvironments, inducing immunogenic cell death, and sensitising radiotherapy and chemotherapy. Consequently, hydrogen therapy based on nanometallic materials has emerged as a novel research focus in cancer treatment. This review systematically elucidates the unique anti-cancer immunobiological effects of hydrogen therapy based on novel nanometallic materials. It meticulously analyses the reversal effects of different metals (Ca, Mg, Fe, Cu, Yb, etc.) in overcoming obstacles within the cancer immune cycle (including antigen presentation, T-cell activation, and resistance mechanisms). It highlights the structure–activity relationships between ‘metal type-specific activity-immune effects’ in the latest hydrogen therapies, elucidates the primary signaling pathways involved in hydrogen-mediated immune regulation, and systematically summarises breakthrough advances in how hydrogen therapy modulates immune responses against tumors. Building upon current cancer treatment trends, this review will synthesise key factors from clinical translation and immunological research perspectives to propose future directions for the field, addressing prevailing challenges.